2023
DOI: 10.3390/mi14030571
|View full text |Cite
|
Sign up to set email alerts
|

SET Kinetics of Ag/HfO2-Based Diffusive Memristors under Various Counter-Electrode Materials

Abstract: The counter-electrode (CE) material in electrochemical metallization memory (ECM) cells plays a crucial role in the switching process by affecting the reactions at the CE/electrolyte interface. This is due to the different electrocatalytic activity of the CE material towards reduction–oxidation reactions, which determines the metal ion concentration in the electrolyte and ultimately impacts the switching kinetics. In this study, the focus is laid on Pt, TiN, and W, which are relevant in standard chip technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…This phenomenon occurs frequently in metal oxide layers, viz., ZnO, SiO 2 , ZrO 2 , and HfO 2 . [167,[182][183][184][185] Moreover, recent studies have demonstrated the growth of the conductive filament in the ZnO layer from the top electrode to the bottom electrode. [186,187]…”
Section: Cation-based Transitionmentioning
confidence: 99%
“…This phenomenon occurs frequently in metal oxide layers, viz., ZnO, SiO 2 , ZrO 2 , and HfO 2 . [167,[182][183][184][185] Moreover, recent studies have demonstrated the growth of the conductive filament in the ZnO layer from the top electrode to the bottom electrode. [186,187]…”
Section: Cation-based Transitionmentioning
confidence: 99%